If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22(g + -2) = 2g + 8 Reorder the terms: 22(-2 + g) = 2g + 8 (-2 * 22 + g * 22) = 2g + 8 (-44 + 22g) = 2g + 8 Reorder the terms: -44 + 22g = 8 + 2g Solving -44 + 22g = 8 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. -44 + 22g + -2g = 8 + 2g + -2g Combine like terms: 22g + -2g = 20g -44 + 20g = 8 + 2g + -2g Combine like terms: 2g + -2g = 0 -44 + 20g = 8 + 0 -44 + 20g = 8 Add '44' to each side of the equation. -44 + 44 + 20g = 8 + 44 Combine like terms: -44 + 44 = 0 0 + 20g = 8 + 44 20g = 8 + 44 Combine like terms: 8 + 44 = 52 20g = 52 Divide each side by '20'. g = 2.6 Simplifying g = 2.6
| 17+3=5w-w | | x^3+8x^2-25x-200=0 | | 2x+2(x+30)=800 | | 5y+17=63 | | 4x+(-3)=-11 | | -8v=7/3 | | 50=5x+y | | f=9/5c-32 | | 4x+8[x-3]=-4+8x | | 12c^2+19c-21=0 | | 22-3x-4=x/4 | | x(2)=30-13x | | -3+6+5a=7a-8a | | 5x+4(-6x+17)=-65 | | 5/2x+31/2x+15 | | 26-13a=13a-26 | | -5(t^2-2t-10)=0 | | 40-8n=-8[2n+1] | | 4(x+1)3(x-3)=2 | | -14=7x/6 | | x/6-2.3=-21.5 | | 4x^2+10x=16 | | -7x+4-3x=-76 | | x/6-2.3=21.5 | | 6x-3y=16 | | y/4=y/3-3 | | (1/6)(6t-7)=(t+7)/12 | | 2(6d+3)=18-3(-3d+16) | | 2(3x-3)=3(2x+4) | | y-5=5 | | 13w=-13w | | 6v+3/5=-2/5v-1/2 |